ANALYSIS OF SMOKING AND COVID-19 MATHEMATICAL MODEL - Temidayo Joseph Oluwafemi; Miswanto Miswanto (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Smoking and COVID-19 have similar effects in the body system, i.e. damaging the airways and lung function. In this work, a mathematical model to study smoking and COVID-19 transmission was studied. The model was proven to have feasible region and it is well-posed mathematically and epidemiologically, the model was further proven to have positive solutions. The basic reproduction number was computed using the next generation method and sensitivity analysis was carried out. The results show that the disease-free equilibrium is locally and globally stable, the most sensitive parameter is the contact rate. The simulation shows that, curtailing rate of contact between exposed, infected individuals and susceptible human population will reduce the spread of the diseases, also giving attention to recovery strategies and controls will reduce to minimum the disease transmission. Therefore, it is recommended that stakeholders should give attention in controlling smoking habits, and prevention and treatment of COVID-19 infected individuals.